Konsep Supervisi dalam Perspektif Islam: Analisis dan Implikasi - Fatimah, Mety; Chabib, Mudzakir; Sriyanta, Sriyanta (TSAQOFAH, 2026)
Educational supervision is a strategic component of educational management that plays a crucial role in improving the quality of instruction and teacher professionalism; however, in practice it is often reduced to administrative and technical activities, thereby neglecting the moral and spiritual dimensions of teachers. This study aimed to examine the concept of supervision from an Islamic perspective and to analyze its implications for the development of contemporary Islamic education. A qualitative approach was employed using a library research method, with data sources consisting of scholarly books, journal articles, and relevant literature discussing educational supervision and Islamic values. The data were analyzed using content analysis to explore the concepts, principles, objectives, and practices of Islamic educational supervision derived from the Al-Qur’an, Hadith, and the history of Islamic education. The findings show that supervision from an Islamic perspective is not only oriented toward enhancing academic performance but also emphasizes the cultivation of akhlaq, responsibility, and the spiritual awareness of educators. Islamic educational supervision is grounded in the principles of trustworthiness (amanah), justice, consultation (musyawarah), and role modeling, and is implemented through a humanistic and participatory approach. This study concludes that integrating Islamic values into supervisory practice has the potential to improve the quality of learning while simultaneously strengthening the sustainable formation of teachers’ religious character within the context of contemporary Islamic education.